Application of Group Investigation Learning Model Based on Among System on Natural Resources Materials to Increase Fifth Grade Students’ Creativity - Yulianti, Widya; Hermita, Neni; Putra, Zetra Hainul (Journal Of Teaching And Learning In Elementary Education, 2024)
This study aims to determine the effect of group investigation based on the Among system on natural resource materials to increase fourth grade students’ creativity. This study uses a quasi-experimental method. This experimental study used two sample groups, namely the experimental group and the control group. The experimental class is a class that is given special treatment, namely the group investigation model based on the Among system, and the control class is given a conventional learning model. Student creativity is measured using a test and also observations during learning. The results showed that (1) the results of the pretest-posttest were normally distributed and homogeneous because the results of the normality and homogeneity test were > 0.05. (2) the results of hypothesis testing using independent sample t-test results obtained significance (2-tailed) is 0.040 and 0.041 where this value is < from 0.05 so Ha is accepted and Ho is rejected. This shows that the application of the Among system-based group investigation model affects fourth grade students’ creativity